Comorbid infections in patients with systemic lupus erythematosus: State-of-the-art - B. S. Belov; S. K. Solovyev; N. G. Klyukvina; G. M. Tarasova; M. V. Polyanskaya M.V. (Научно-практическая ревматология)
In modern rheumatology, comorbid infections (CIs) have a significant impact on morbidity and mortality of patients with systemic lupus erythematosus (SLE). The increased susceptibility of SLE patients to infections is associated with various immune disorders. A number of risk factors for CIs in SLE, which are related to the disease and its treatment, have been identified. However, despite the fact that there are a sufficient number of these factors, the contribution of each of them varies considerably with the cohort of examined SLE patients. The paper considers the epidemiological, clinical, and laboratory characteristics of some bacterial and viral CIs in patients with SLE in current clinical practice. It underlines the importance of primarily influenza and pneumococcal vaccination in patients with SLE since among them the risk of deaths from lower respiratory tract infections is quite high. The ways of further investigations in the framework of the problem under consideration are outlined.